Decadal variability of aerosol optical depth in Europe and its relationship to the temporal shift of the North Atlantic Oscillation in the realm of dimming and brightening - Chiacchio, Marc; Ewen, Tracy; id_orcid:0 000-0002-7751-5235; Wild, Martin; Chin, Mian; Diehl, Thomas (Journal of Geophysical Research, 2011)
ISSN:0148-0227 ISSN:2169-897X